Books and journals reviews - Rátiva Velandia, Marlén; Gómez Velasco, Nubia Yaneth; Torres Aguilar, Morelos; Fernández Hormiga, Gresia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this section you will find reviews of books and journals related to the history of the Latin American education.